Pre-existing Liver Diseases and On-Admission Liver-Related Laboratory Tests in COVID-19: A Prognostic Accuracy Meta-Analysis With Systematic Review - Váncsa, Szilárd; Hegyi, Péter Jeno; Zádori, Noémi; Szakó, Lajos; Vörhendi, Nóra; Ocskay, Klementina; Földi, Mária; Dembrovszky, Fanni; Dömötör, Zsuzsa Réka; Jánosi, Kristóf; Rakonczay, Zoltán; Hartmann, Petra; et al. (Frontiers in Medicine, 2020)
Background We aimed to perform a systematic search and meta-analysis to evaluate the prognostic value of on-admission liver function tests and pre-existing liver diseases on the clinical course of coronavirus disease 2019 (COVID-19). Methods The study was registered on PROSPERO (CRD42020182902). We searched five databases between 01/01/2020 and 23/04/2020. Studies that reported on liver-related comorbidities and/or laboratory parameters in patients with COVID-19 were included. The main outcomes were COVID-19 severity, intensive care unit (ICU) admission, and in-hospital mortality. Analysis of predictive models hierarchical summary receiver-operating characteristic (HSROC) was conducted with a 95% confidence interval (CI). Results Fifty studies were included in the meta-analysis. High specificity was reached by acute liver failure associated by COVID-19 (0.94, CI: 0.71–0.99), platelet count (0.94 CI: 0.71–0.99) in the case of mortality; chronic liver disease (CLD) (0.98, CI: 0.96–0.99), platelet count (0.82, CI: 0.72–0.89) in the case of ICU requirement; CLD (0.97, CI: 0.95–0.98), chronic hepatitis B infection (0.97, CI: 0.95–0.98), platelet count (0.86, CI: 0.77–0.91), alanine aminotransferase(ALT) (0.80, CI: 0.66–0.89) and aspartate aminotransferase(AST) (0.84, CI: 0.77–0.88) activities considering severe COVID-19. High sensitivity was found in the case of C-reactive protein(CRP) for ICU requirement (0.92, CI: 0.80–0.97) and severe COVID-19 (0.91, CI: 0.82–0.96). Conclusion On-admission platelet count, ALT, AST activity and CRP concentration, and presence of acute and chronic liver diseases predicted severe course of COVID-19. To highlight, preexisting liver diseases or acute liver injury associated by SARS-CoV-2 infection plays an important role in the prediction of mortality.